Ms. Marvel. Vol. 5, Super famous - Wilson, G. Willow, 1982- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2016)
"She's your new favorite. She's everyone's new favorite. And now she's joining the big leagues. Look out world, Kamala Khan is an Avenger! But is she really cut out to be one of Earth's Mightiest Heroes? Saving the world is important, but Jersey City still needs its protector--and a development company that co-opted Ms. Marvel's face for its project has more in mind for gentrification than just real estate! Can Kamala take down the evil suits destroying her home without ruining her grades and personal life? "--Description from forbiddenplanet.co.uk.